2012
DOI: 10.1002/nag.2112
|View full text |Cite
|
Sign up to set email alerts
|

Using modified state surface approach to select parameter values in the Barcelona basic model

Abstract: The Barcelona basic model (BBM) successfully explained many key features of unsaturated soils and received extensive acceptance. It is also one of the few elastoplastic constitutive models for unsaturated soils that have been implemented within finite element codes and applied to the analysis of real boundary value problems. The BBM was proposed in incremental forms according to theories of soil plasticity in which individual aspects of the isotropic virgin behavior are controlled by multiple parameters, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…The maximum settlement regarding to self-weight occurred at mid-height of the embankment as the model was constructed gradually and the accumulative displacement was reported since the placement of each level. The results in both studies [37] with the present research) match very well, as are being observed in Fig. 7.…”
Section: Numerical Analysessupporting
confidence: 91%
“…The maximum settlement regarding to self-weight occurred at mid-height of the embankment as the model was constructed gradually and the accumulative displacement was reported since the placement of each level. The results in both studies [37] with the present research) match very well, as are being observed in Fig. 7.…”
Section: Numerical Analysessupporting
confidence: 91%
“…It was found that the initial yield stress for most soil specimens can be refined to be 200 kPa, and analysis was performed again for the new data. The numerical approach as discussed in Zhang and Xiao was used to solve the X=leftleftN0leftλ0leftβleftrleftpcT. Table shows the final results for the calibrated model parameters.…”
Section: Verifying Shape Of Yield Curve For Unsaturated Soils Using Rsupporting
confidence: 72%
“…Wheeler and Sivakumar [27] experimentally verified the uniqueness of the virgin loading void ratio surface for unsaturated soils. Taking advantage of the uniqueness of the virgin loading surface and bypassing the incremental approach, the MSSA is a macro-level framework that simplifies the process of constitutive modeling and creates a clear guide for model development [24], model calibration [28], and comparisons across existing constitutive models [16,24,29]. Under isotropic stress conditions, the MSSA is illustrated by Fig.…”
Section: Overview Of the Mssamentioning
confidence: 99%